A Qualitative Analysis of Why Managers Use Target Setting and Measurement Mechanisms in Pakistani Organisations - Faisal, Shameen (2017)
Researches on target setting and measurements have gained immense popularity among management academics. Most studies have been carried out to inspect the positive impact of target setting on employee and organisational performances. However, seldom work has been published regarding this topic from a managerial perspective. Therefore, this study examines the rationale and theory behind the usage of target setting and measurement mechanisms being a profoundly famous choice around the globe. A qualitative analysis was carried out, based on the managers of corporate organisations in Lahore, Pakistan. In-depth interview analysis of 8 participants was conducted. The results of the study were depicted through three main themes: individual performance, management, and negative externalities of target setting.